Teaching beliefs of the professors in the Autonomous University of Aguascalientes - Miramontes Zapata , Silvia del Carmen (Consorcio de Universidades Mexicanas A.C., 2018)
Teacher ́s beliefs are the main factor to understand the educational practice. The teaching style is closely related to the representations that a teacher has about the teaching contents, the curriculum, the school organization and the learning process of the students. Among other things, in order to analyze the educational practice of teachers from Autonomous University of Aguascalientes (UAA), the current research was carried out, its objectives were: 1. To describe the professionalization and teachers’ training characteristics such as years of experience, time devoted to this activity, academic degree, specialty area, subjects that are taught as well as his/ her main function in the institution. 2. To know the predominant educational perspectives of teachers from UAA without separating the perspectives components (beliefs, purposes and actions). 3. To compare the different predominant perspectives with some characteristics which are typical aspects of professionalization and teachers training. The sample consisted of 73 teachers of both sexes that are part of the staff; the Teaching Perspectives Inventory was administered. Some of the findings suggest that the perspective of transmission is the predominant one, this means that for UAA teachers, a good teacher is who masters the subject contents, has clear objectives, presents a convenient feedback to his/ her students and has a strong commitment with the contents.